Isolation and Propagation of Mesenchymal Stem Cells from the Lacrimal Gland - You, Samantha (Association for Research in Vision and Ophthalmology, Inc., 2011)
PURPOSE. Previously, it was reported that the murine lacrimal gland is capable of repair after experimentally induced injury and that the number of stem/progenitor cells was increased during the repair phase (2–3 days after injury). The aim of the present study was to determine whether these cells can be isolated from the lacrimal gland and propagated in vitro. METHODS. Lacrimal gland injury was induced by injection of interleukin (IL)-1, and injection of saline vehicle served as control. Two and half days after injection, the lacrimal glands were removed and used to prepare explants or acinar cells for tissue culture. Cells derived from the explants and the acinar cells were grown in DMEM supplemented with 10% fetal bovine serum. Cells were stained for the stem cells markers, nestin, vimentin, ABCG2, and Sca-1. Cell proliferation was measured using an antibody against Ki67 or a cell-counting kit. The adipogenic capability of these cells was also tested in vitro. RESULTS. Results show that nestin-positive cells can be isolated from IL-1–injected, but not saline-injected, lacrimal glands. A population of nestin-positive cells was also positive for vimentin, an intermediate filament protein expressed by mesenchymal cells. In addition, cultured cells expressed two other markers of stem cells, ABCG2 and Sca-1. These cells proliferated in vitro and can be induced to form adipocytes, attesting to their mesenchymal stem cell property. CONCLUSIONS. Murine lacrimal glands contain mesenchymal stem cells that seem to play a pivotal role in tissue repair.